Mapping Worldwide Antibiotic Use in Dental Practices: A Scoping Review - Fatemeh Soleymani; Carlos Pérez-Albacete Martínez; Mehrdad Makiabadi; José Eduardo Maté Sánchez de Val (MDPI AG, 2024)
Antibiotic resistance is a critical issue today, necessitating the monitoring of antibiotic usage across various sectors. To determine the defined daily doses (DDDs) of antibiotics prescribed by dentists globally, a comprehensive search was conducted in PubMed, ProQuest, ScienceDirect, Web of Science, Scopus, and EBSCOhost, resulting in the inclusion of 15 documents in this scoping review. The DDD per 1000 inhabitants per day (DID) for oral antibiotics prescribed by dentists for the studied countries was generally below 2.11, with the exception of South Korea, which had a DDD per 1000 patients per day (DPD) of less than 6.97. Most countries, except Croatia and Belgium, demonstrated a decreasing trend in DID before the COVID-19 pandemic, but restrictions during the pandemic led to an increase in these numbers. Penicillin-derived antibiotics were the most commonly prescribed antibiotic among dentists in most countries. This study highlights significant gaps and missing data regarding antibiotics prescribed by dentists worldwide. However, it also indicates that the publication of guidelines, education, and evaluation of antibiotic use can lead to more controlled and appropriate prescriptions among dental professionals.